The Relations between QFII Holdings and Company Performance: Evidence from China’s A-Share Listed Companies - Xiong Wang; Shuanghong Zhou; Wenqian Fang (Discrete Dynamics in Nature and Society)
In order to investigate the relations between qualified foreign institutional investors (QFII) holdings and the performance of the A-share listed companies and effectively distinguish between QFIIs’ ability to identify value companies and their ability to enhance company value, this paper empirically examines the relations between QFII holdings and company performance using Chinese annual report data from 2010 to 2012. The results show that QFIIs have strong ability in identifying value companies. However, the effect of QFII holdings on company performance improvement is mainly manifested in the short term, and the long-term effect is insignificant. In the long run, QFIIs may not be considered as “value boosters,” implying that it is unlikely for QFIIs to greatly enhance company value and help the invested companies to improve the level of governance and their long-term performance.